The shaping of knowledge: communication of meaning through museum exhibition design / Shamsidar Ahmad … [et al.] - Ahmad, Shamsidar; Abbas, Mohamed Yusoff; Mohd. Taib, Mohd. Zafrullah; Masri, Mawar (Universiti Teknologi MARA Cawangan Selangor, 2018)
The primary objective of museum management in shaping of knowledge can be achieved by a communication of meaning through quality displays of the permanent collection or temporary exhibitions, the specimens of a continent or the interactive apparatus of science. This paper looks at research derived primarily from the museum scholars and experts with academics working in the field of visitor studies towards developing exhibits that facilitated visitor learning. These findings are recast the approach in order to offer an integrated framework for visitor behavior has implications for service management of the service encounter at the museum in Malaysia.